Current State and Development of the Restaurants Business in Luang Prabang City - THIDAVANH, Soulichan; SOMSAMONE, Vilayphone; OUTTHACHACK, Sindavone; VONGMANICHANH, nouy (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The restaurant business is a component of tourism promotion in LuangPrabang, especially because of its role in providing food services to both domestic and foreign visitors to LuangPrabang. The restaurant business is also a business unit that can create jobs and income for local employment. This study aims to study the current state and development of the restaurant business in Luang Prabang. The study methodology is a mixed research that collects data from two sources: primary and secondary data. The population and the main sample groups used for the study were the restaurant business units and some related departments. The study found that the restaurant situation in LuangPrabang has two aspects: the restaurant serves international tourists and the general restaurant serves both tourists and international tourists. The restaurant serves international tourists mainly with the LuangPrabang World Heritage Area, while the rest of the restaurant is common in the capital, including the heritage area. The role and importance of the store in terms of job creation for the Lao people is minimal for the Lao people, seeing the number of restaurant-related professionals increasing every year as well as employment in this sector as an opportunity to create employment for the disadvantaged and women.